FENOMENA PENGGUNAAN FACEBOOK SEBAGAI AJANG EKSISTENSI DIRI REMAJA DI KOTA BATAM - Ardhy, Ardhiya Annisa; Syafi'i, Muhammad (SCIENTIA JOURNAL, 2020)
Facebook is one of the most popular social media, even in early 2019, Indonesia ranks 4th in the number of Facebook users in the world for total of 120 million or 44.94 percent of the total population. Facebook was created by Mark Zuckerberg and can attract the attention of many users of various ages. Facebook has a variety features: sharing status, photos, stories, and even marketplace. The trend to always appear on social media like Facebook makes people continuously upload their status, and photos. Not only to show their activity, but they expect to get a lot of likes for everything they upload. The purpose of the research is to know how the phenomenon of the use of Facebook as a place to get the self-existence of teenagers in Batam city. This type of research uses descriptive qualitative methods . Data collection techniques are conducted by observation, in-depth interviews, and study of libraries from various sources of research materials. The samples used in this study were obtained by the Snowball Sampling technique. The results of this study showed that there was a hyperreality in most teenagers in the city of Batam who wanted to exist on their social media Facebook.